Prosthetic rehabilitation of patient with maxillofacial defect by hollow bulb obturator (Health Renaissance, 2014)
Introduction: Post-surgical maxillary defect is mostly repaired by the use of an obturator, which is often quite heavy due to the extension into the defect that is better relieved by making it hollow. Objective: To fabricate hollow bulb obturator in simple way. Case: An 85 year old man was referred from ENT department after hemimaxillectomy to remove squamous cell carcinoma, for obturator prosthesis and was treated with hollow bulb obturator prosthesis. Conclusion: The hollow bulb reduces the weight of prosthesis making is comfortable for the patient. DOI: http://dx.doi.org/10.3126/hren.v11i3.9656 Health Renaissance 2013;11(3):284-286